Montreal's Italians and the Socio-Economy of Settlement, 1900-1930: Some Historical Hypotheses - Ramirez, Bruno (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1981)
As the pattern of Italian immigration to Montreal changed from one made up predominantly of sojourners to one of permanent settlement, important changes occurred both in the composition of that immigrant population (sex ratio, age structure, etc.) and in its internal organization (residential patterns, kinship and paese-based network). These changes made possible the enactment of familial economic strategies characterised by the use of extra-market resources to complement the means of life deriving from earnings. Though the magnitude of this practice escapes precise quantification, its occurrence seems to have been so widespread among Italian immigrants as to constitute a socio-economic subsystem existing alongside the official market system. Moreover, in this sphere of economic behavior, Italian immigrants enjoyed a greater autonomy in their use of time and space and thus could more freely resort to their cultural values as an important resource for their adaptive strategies. More detailed analysis of the socio-economy of settlement may throw important light on the specificity of the ethnic cohesion characterising Italian immigrant communities in Montreal during those years.